2012
DOI: 10.4028/www.scientific.net/msf.730-732.153
|View full text |Cite
|
Sign up to set email alerts
|

Synthesising Carbo-Nitrides of some D-Group Transition Metals Using a Solar Furnace at PSA

Abstract: Carbo-nitride synthesis was undertaken using a solar furnace at PSA in flowing N2/Ar gas mixture under total pressure 1 atm and processing temperatureT= 1600°C for some d-group transition elements (Ti; Zr, V, Nb, Mo, W) starting from 1.5G/M (graphite/metal powder mixture with mole ratio 1.5:1) compact to ensure co-presence of free carbon with the reaction product. Clear X-ray diffraction (XRD) evidence of formation of carbo-nitride was detected for Ti (IVa group metal) showing higher N content in the carbo-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The optical configuration in the solar furnace solar furnace at Plataforma Solar de Almería was basically identical to the one we have been using since 1997 and thence the details might be referred to elsewhere [15][16][17][18][19][20][21][22][23][24][25]. The current solar furnace solar furnace system at Plataforma Solar de Almería was with much improved monitoring systems as well as with upgraded quality of optical components (reflectors and concentrator).…”
Section: Methodsmentioning
confidence: 73%
“…The optical configuration in the solar furnace solar furnace at Plataforma Solar de Almería was basically identical to the one we have been using since 1997 and thence the details might be referred to elsewhere [15][16][17][18][19][20][21][22][23][24][25]. The current solar furnace solar furnace system at Plataforma Solar de Almería was with much improved monitoring systems as well as with upgraded quality of optical components (reflectors and concentrator).…”
Section: Methodsmentioning
confidence: 73%
“…Noting difficulty of synthesizing nitride of VIa-group metals (Hägg, 1930;Mills, 1970Mills, , 1972Toth, 1971;Fromm and Gebhardt, 1976;Yoshizawa et al, 1977;Jehn and Ettmayer, 1978;Pierson, 1996;Ren et al, 1999;Inumaru et al, 2008;Shohoji et al, 2011Shohoji et al, , 2013aShohoji et al, , 2013b in conventional electric furnace even in uncracked NH 3 gas, the demonstrated option in the present work to undertake nitriding in NH 3 gas stream under concentrated solar irradiation seem to be of pragmatic convenience to synthesize precursor nitride powders to be subjected to further subsequent nitriding process.…”
Section: Discussionmentioning
confidence: 92%